An adaptation of the Psychological Capital Questionnaire for the sports environment - Erika Borrajo; Garazi Azanza; Itziar Urquijo , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Identifying the psychological strengths of athletes is necessary to improve their performance. With the objective of comprehensively assessing those, the present study aimed to adapt and validate the Spanish version of the PCQ (Azanza et al., 2014) in a sample of athletes from different disciplines. Participants were 540 athletes recruited to participate in the study with the assistance of university students. The factor structure of the SPCQ was tested with a confirmatory factor analysis (CFA), and a correlational analysis was carried out to analyze the relationship between Sport PsyCap and personality. Statistical analyses showed that the questionnaire obtained adequate psychometric properties regarding reliability, construct validity and convergent validity. These confirmed the existence of four first-order factors (self-efficacy, optimism, hope, and resilience) and a second-order factor (PsyCap), following the structure of both the original questionnaire (Luthans et al., 2007), and the version adapted to the Spanish sample (Azanza et al., 2014). The SPCQ is presented as a suitable way to measure psychological capital both in the field of research and professional practice, offering a reliable tool for the identification and subsequent intervention in different psychological aspects that can improve performance.